Museum of Black Civilizations: Time is Running Out - (:unkn) unknown (My University, 2022)
The Museum of Black Civilizations is above all the expression of a need specific to a specific and precise historical context. Its origin is rooted in the emergence of Negritude movement confronted with the Western denial of Black Civilizations legacies, technologies and cultural histories., Faced with theoretical constructs that defined humans experiences through “soon to be obsolete” racial categories in the early twentieth century, Black activists and intellectuals initiated common transcontinental strategies shaped through series of pan-African meetings. They include the Pan-African Conference in London (23-25 July 1900), the Pan-African Congress in Manchester (15-21 October 1945) and the Accra Conference (15-22 April 1958). In addition to these politically charged demonstrations against inequality, the two Congresses of Black Writers and Artists (Paris 1956 and Rome 1959) mark the birth of discourses that add a cultural and artistic dimension to these already global dynamics.
Keywords: African Research